A clean energy assessment of early adopters in electric vehicle and solar photovoltaic technology: Geospatial, political and socio-demographic trends in New York. (10th April 2019) - Araújo, Kathleen; Boucher, Jean Léon; Aphale, Omkar
Abstract: We studied electric vehicles and solar photovoltaic technology diffusion in the State of New York to shed light on the attributes of early adopters of clean energy. Using geospatial, regression, and cluster analyses of zip code level and county indicators, we analyzed trends with locational, political and socio-demographic profiles to identify areas of convergence and divergence in adoption patterns. In line with elements of the literature, we confirmed the importance of income and median home value for a relatively under-studied region in early-staged, electric vehicle and solar photovoltaic technology adoption. We also found that political orientation and age tendencies are more nuanced and less predictive. However, we noted key, adoptive tendencies among those aged 30-44 and above 59 for solar photovoltaics. Moreover, southeastern counties near New York City, particularly on Long Island, are identified as critical niches in the early-staged diffusion of clean energy. This study highlights observed tendencies from diverse methodological approaches in clean technology diffusion, providing a basis for a fuller set of technology and policy studies for New York or similarly-focused regions.